2011
DOI: 10.1245/s10434-011-1836-7
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of MMP-9 Over MMP-2 in HCC Invasiveness and Recurrence of Hepatocellular Carcinoma After Curative Resection

Abstract: MMP-9 is superior to MMP-2 for the prediction of tumor recurrence and survival in HCC patients after surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 35 publications
6
68
0
Order By: Relevance
“…The majority of clinical data had revealed correlations between the expression of MMPs and advanced tumor stages, invasion, metastasis and decreased survival rates (46). Previous studies have demonstrated that several MMPs are overexpressed in HCC and that high expression levels of MMPs are associated with cancer progression and metastasis (47)(48)(49). It was therefore suggested that inhibitors of MMP activity may be investigated for the prevention or reduction of tumor metastasis.…”
Section: Mmp-9 Is a Direct Target Gene Of Mir-133a In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of clinical data had revealed correlations between the expression of MMPs and advanced tumor stages, invasion, metastasis and decreased survival rates (46). Previous studies have demonstrated that several MMPs are overexpressed in HCC and that high expression levels of MMPs are associated with cancer progression and metastasis (47)(48)(49). It was therefore suggested that inhibitors of MMP activity may be investigated for the prevention or reduction of tumor metastasis.…”
Section: Mmp-9 Is a Direct Target Gene Of Mir-133a In Hccmentioning
confidence: 99%
“…In addition, these studies revealed an association between the overexpression of MMP-2 or -9 and the invasion and metastasis of HCC. Increased levels of MMP-9 in HCC also correlate with increased tumour recurrence and metastasis following resection (48,49,52). Hayasaka et al (53) reported that MMP-9 plasma levels were upregulated in HCC patients, particularly in patients who presented with macroscopic portal vein invasion, which suggested that MMP-9 may serve as a marker for transformation and invasion in HCC or as a therapeutic target for the inhibition of metastasis in HCC.…”
Section: Mmp-9 Is a Direct Target Gene Of Mir-133a In Hccmentioning
confidence: 99%
“…Matrix metalloproteinases-2 (MMP-2) and MMP-9, which represent 72 kD and 92 kD type IV collagenases, respectively, degrade the basement membrane of normal cells and result in tumor invasion and subsequent metastasis. The detection of high expression levels of MMP-2 and MMP-9 in HCC has been suggested as a biomarker for poor prognosis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-2 and MMP-9 are two members of the MMP family and they are the primary enzymes that degrade diffusely basal membrane type IV collagen (21). Early studies have demonstrated that MMP-2 and MMP-9 exhibited increased expression in patients with HCC, which may be a prediction of tumor recurrence and survival in patients with HCC following surgical resection (22,23). In the current study, the effects of emodin on MMP-2 and MMP-9 expression in cells were investigated and the results suggest that emodin significantly downregulated MAPKs are serine-threonine protein kinases that mediate a wide variety of cellular behaviors, including proliferation, differentiation, apoptosis, migration and invasion (24).…”
Section: Discussionmentioning
confidence: 99%